Seeking a deeper understanding of 'distributed health literacy': A systematic review. (18th February 2022) - Muscat, Danielle M.; Gessler, Danielle; Ayre, Julie; Norgaard, Ole; Heuck, Iben R.; Haar, Stefanie; Maindal, Helle T.
Abstract: Background: Previous research suggests that it would be useful to view health literacy as a set of 'distributed competencies', which can be found dispersed through the individual's social network, rather than an exclusively individual attribute. However, to date there is no focused exploration of how distributed health literacy has been defined, conceptualized or assessed in the peer‐reviewed literature. Aims: This systematic review aimed to explore: (1) definitions and conceptual models of distributed health literacy that are available from the peer‐reviewed literature; and (2) how distributed health literacy has been measured in empirical research. Methods: We searched MEDLINE, Embase, CINAHL, PsycInfo, Scopus, ERIC and Web of Science using truncated versions of the keywords 'literacy' and 'distributed' (within five words' distance). We collated the definitions and conceptual models of distributed health literacy, and report on how health literacy has been measured in empirical research studies. Findings related to distributed health literacy from included manuscripts were synthesized using thematic synthesis. Results: Of the 642 studies screened, 10 were included in this systematic review. The majority were empirical manuscripts reporting on qualitative research in one of five countries, with two reviews, one conceptual analysis and one quantitative study. Edwards' definition of distributed health literacy, which emphasizes the health literacy abilities, skills and practices of others that contribute to an individual's level of health literacy was widely applied in a variety of clinical and geographical settings. However, we did not identify any quantitative instruments which directly measured distributed health literacy. There was significant variability in questions used to explore the concept qualitatively, and discrepancies across studies in regard to (a) what constitutes distributed health literacy and what does not (e.g., general social support), and (b) the relationship between distributed health literacy and other constructs (e.g., public health literacy). Conclusion: Although there is a widely applied definition of distributed health literacy, our review revealed that the research space would benefit from the development of the concept, both theoretically for example via conceptual distinctions between distributed health literacy and other types of social support, and empirically for example through the development of a quantitative measurement instrument. Patient or Public Contribution: This paper is a systematic review and did not involve patients or the public.